Single-cell RNA sequencing reveals cell landscape following antimony exposure during spermatogenesis in Drosophila testes - Yu, Jun; Fu, Yangbo; Li, Zhiran; Huang, Qiuru; Tang, Juan; Sun, Chi; Zhou, Peiyao; He, Lei; Sun, Feiteng; Cheng, Xinmeng; Ji, Li; Yu, Hao; et al. (Cell Death Discovery, 2023)
Antimony (Sb), is thought to induce testicular toxicity, although this remains controversial. This study investigated the effects of Sb exposure during spermatogenesis in the Drosophila testis and the underlying transcriptional regulatory mechanism at single-cell resolution. Firstly, we found that flies exposed to Sb for 10 days led to dose-dependent reproductive toxicity during spermatogenesis. Protein expression and RNA levels were measured by immunofluorescence and quantitative real-time PCR (qRT-PCR). Single-cell RNA sequencing (scRNA-seq) was performed to characterize testicular cell composition and identify the transcriptional regulatory network after Sb exposure in Drosophila testes. scRNA-seq analysis revealed that Sb exposure influenced various testicular cell populations, especially in GSCs_to_Early_Spermatogonia and Spermatids clusters. Importantly, carbon metabolism was involved in GSCs/early spermatogonia maintenance and positively related with SCP-Containing Proteins, S-LAPs, and Mst84D signatures. Moreover, Seminal Fluid Proteins, Mst57D, and Serpin signatures were highly positively correlated with spermatid maturation. Pseudotime trajectory analysis revealed three novel states for the complexity of germ cell differentiation, and many novel genes (e.g., Dup98B) were found to be expressed in state-biased manners during spermatogenesis. Collectively, this study indicates that Sb exposure negatively impacts GSC maintenance and spermatid elongation, damaging spermatogenesis homeostasis via multiple signatures in Drosophila testes and therefore supporting Sb-mediated testicular toxicity.